2018
DOI: 10.1093/cercor/bhy176
|View full text |Cite
|
Sign up to set email alerts
|

Brain Activity Tracks Population Information Sharing by Capturing Consensus Judgments of Value

Abstract: Information that is shared widely can profoundly shape society. Evidence from neuroimaging suggests that activity in the ventromedial prefrontal cortex (vmPFC), a core region of the brain's valuation system tracks with this sharing. However, the mechanisms linking vmPFC responses in individuals to population behavior are still unclear. We used a multilevel brain-as-predictor approach to address this gap, finding that individual differences in how closely vmPFC activity corresponded with population news article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 35 publications
2
18
0
Order By: Relevance
“…Interestingly, this brain-as-predictor relationship was significant for emotional responses measured on different days in different contexts. More generally, our findings further add to the growing literature that psychological studies broaden the scope beyond the laboratory for extended validity and generalizability to real-world outcomes (Kingstone et al, 2003; Doré et al, 2018; Schmälzle et al, 2017).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Interestingly, this brain-as-predictor relationship was significant for emotional responses measured on different days in different contexts. More generally, our findings further add to the growing literature that psychological studies broaden the scope beyond the laboratory for extended validity and generalizability to real-world outcomes (Kingstone et al, 2003; Doré et al, 2018; Schmälzle et al, 2017).…”
Section: Discussionsupporting
confidence: 69%
“…In addition to these predictions for within-session physiological responses, our core analysis examined the relationship between the sessions, including behavioral responses (emotional intensity ratings, task performance, and self-report anxiety) and physiology from different modalities (brain connectivity and HRV). For the behavioral responses, we expected that emotional reactivity would be heightened during the immersive experience (Parsons, 2015); however, the literature is mixed regarding how well behavior in stationary, laboratory tasks predicts task performance when the stimuli have features more typical of real-world environments (Smilek et al, 2008; Hasson et al, 2010; Gramann et al, 2011; Schmälzle et al, 2017; Doré et al, 2018; Wasylyshyn et al, 2018). For the physiological measurements, some recent work has suggested that a stress response can rapidly couple brain and heart responses (Sakaki et al, 2016), but it was unclear whether this relationship would be observed between laboratory and simulation environments, especially with a temporal delay across days.…”
Section: Introductionmentioning
confidence: 99%
“…To distinguish between the trade-off and parallel-processes hypotheses (Table 1), we conducted a within-subject experiment in which participants were exposed to 80 New York Times (NYTimes) articles in different conditions, which asked participants to consider either broad-or narrowcasting with others, while we monitored their neural activity using fMRI. We have reported on orthogonal analyses of the same neural data elsewhere to understand the neural correlates of individual and population-level sharing (Scholz et al, 2017;Doré et al, 2018), averaging across (and thereby ignoring differences between) narrow-and broadcasting situations. Here, for the first time, we distinguish between the processes involved in decisions to share when offered the opportunity to narrow-and broadcast.…”
Section: Methodsmentioning
confidence: 99%
“…And perhaps -with a bit of courage -we may even begin to provide an empirical constitution to the deeper philosophical questions that humans have wrestled with for millennia: What makes us unique and different from non-human animals 240,302 ? How do we represent abstract concepts such as value to ourselves 303 and others 304 ? How are representations transmitted throughout the brain or reconfigured based on new knowledge 305 ?…”
Section: Conclusion and Future Directions In The Neurophysics Of Bramentioning
confidence: 99%